SEE characteristics of small feature size devices by using laser backside testing - 封国强 上官士鹏 马英起 韩建伟 (Journal of semiconductors, 2012)
This paper presents single event upset （SEU） and single event latch-up （SEL） characteristics of small feature size devices by laser backside testing method, which is dedicated to dealing with the increasing metal layers on the front side of integrated circuits. The influence of test data pattern on SEU threshold and cross-section is investigated. The supply current state of micro latch-up for deep sub-micron SRAM is described. The laser energy thresholds were correlated to heavy ion thresholds LET to determine an empirical relationship between laser energy threshold and heavy ion LET. This empirical relationship was used to estimate the equivalent laser LETs for devices fabricated in small feature sizes. Moreover, the SEU of a Power PC CPU fabricated with 90 nm SOI CMOS process has been tested, which indicates that the laser backside method could be used to evaluate SOl small feature size devices.